(untitled) (Scientific Journal of Research Studies in Future Psychology, 2025)
This study aimed to investigate the role of family functioning and depression in predicting the tendency to use drugs in high school students in Borazjan. The statistical population included all high school students in Borazjan in the academic year 2014-2015, from which a sample of 300 people (147 girls and 153 boys) were selected using multistage cluster random sampling. The Family Assessment Questionnaire (FAD), Beck Depression Inventory (BDI-II), and Addiction Proneness Scale (APS) were used to collect data. The collected data were analyzed using Pearson correlation coefficient, multiple regression analysis, and independent t-test. The results of the regression analysis showed that family functioning and depression are significant predictors of the tendency to use drugs (p<0.001, f=759.844) and explain a total of 83.5% of the variance in the tendency to use drugs. Family functioning as a whole also had a significant predictive power for substance use tendencies (r=0.913). A positive and significant correlation was also observed between the level of depression and substance use tendencies (r=0.829). In addition, significant gender differences were observed in family functioning and depression; such that female students reported more favorable family functioning, while male students had higher levels of depression and substance use tendencies. Overall, the findings showed that favorable family functioning has an important protective role against substance use tendencies and depression can be recognized as one of the important risk factors in this regard. Also, the gender differences obtained highlight the need to pay attention to preventive programs and interventions tailored to the characteristics of each gender.